A magnetar parallax. Issue 3 (21st August 2020) - Ding, H; Deller, A T; Lower, M E; Flynn, C; Chatterjee, S; Brisken, W; Hurley-Walker, N; Camilo, F; Sarkissian, J; Gupta, V
ABSTRACT: XTE J1810−197 (J1810) was the first magnetar identified to emit radio pulses, and has been extensively studied during a radio-bright phase in 2003–2008. It is estimated to be relatively nearby compared to other Galactic magnetars, and provides a useful prototype for the physics of high magnetic fields, magnetar velocities, and the plausible connection to extragalactic fast radio bursts. Upon the rebrightening of the magnetar at radio wavelengths in late 2018, we resumed an astrometric campaign on J1810 with the Very Long Baseline Array, and sampled 14 new positions of J1810 over 1.3 yr. The phase calibration for the new observations was performed with two-phase calibrators that are quasi-colinear on the sky with J1810, enabling substantial improvement of the resultant astrometric precision. Combining our new observations with two archival observations from 2006, we have refined the proper motion and reference position of the magnetar and have measured its annual geometric parallax, the first such measurement for a magnetar. The parallax of 0.40 ± 0.05 mas corresponds to a most probable distance $2.5^{\, +0.4}_{\, -0.3}$  kpc for J1810. Our new astrometric results confirm an unremarkable transverse peculiar velocity of ≈200 $\rm km~s^{-1}$ for J1810, which is only at the average level among the pulsar population. The magnetar proper motion vector points back to the central region of a supernova remnant (SNR) at a compatible distance at ≈70 kyr ago, but a direct association is disfavoured by the estimated SNR age of ∼3 kyr.